Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I was wondering how to get the cumulative distribution function of a sum of two random binomial variables.

X + Y, where X has n=15 trials and Y has m=15 trials and probability=0.2 for both

P(15<= X+Y <= 20) how would I express this as a cumulative distribution function?

Can I just add their probability mass functions Px(X) and Py(Y) and then get the CDF from there or do I need to go from joint distribution formulas?

Any help would be greatly appreciated!

Thanks.

share|improve this question
    
If $X$ is Binomial$(n,p)$, $Y$ is Binomial$(m,p)$, and if $X$ and $Y$ are $independent$, then $X+Y$ is Binomial$(n+m,p)$. –  David Mitra Jan 30 '12 at 15:36
    
so this would just be another function with trials = n+m = 30 and probability p=0.2, I could just express it as P(Z) where Z=X+Y correct? –  Alistair Jan 30 '12 at 15:39
    
Yes, but you need independence of $X$ and $Y$. –  David Mitra Jan 30 '12 at 15:42
    
Thanks David, how can I give you reputation points based on your comments? : ) –  Alistair Jan 30 '12 at 15:46

2 Answers 2

up vote 6 down vote accepted

Assuming that $X$ and $Y$ are independent, you can use the following, standard, result:

Let $X_1$ and $X_2$ be discrete, independent random variables with ${\rm dist }(X_1)={\rm B}(n,p)$ and ${\rm dist }(X_2)={\rm B}(m,p)$, where $B(n,p)$ denotes the Binomial distribution with $n$ trials and success factor $p$.

By independence, it would seem that the total number of successes in $n$ trials of $X_1$ and $m$ trials of $X_2$ should be a binomial variable with parameters $n+m$ and $p$. We now show that this is, indeed, the case.

Let $Y=X_1+X_2$. We will find the probability mass function of $Y$. Since $Y$ is the total number of successes in $n$ trials of $X_1$ and $m$ trials of $X_2$, the random variable $Y$ takes the values $0$, $1$, $\ldots\,$, $n+m$. Using the Convolution Theorem, for $0\le k\le n+m$, we have:

$$ \eqalign{ p_Y(k)&=\sum_{i=0}^kP[X_1=i,X_2=k-i]\cr &=\sum_{i=0}^kP[X_1=i]\cdot P[ X_2=k-i]\cr &=\sum_{i=0}^k{n\choose i}(1-p)^{n-i}p^i\cdot{m\choose k-i}(1-p)^{m-(k-i)}p^{k-i}\cr % &=\sum_{i=1}^k{n\choose i}{m\choose k-i}(1-p)^{m+n}p^{k}\cr &=(1-p)^{m+n-k }p^{k}\sum_{i=0}^k{n\choose i}{m\choose k-i}\cr &={m+n\choose k}(1-p)^{m+n-k}p^{k }. } $$ Thus, ${\rm dist }(X_1+X_2)={\rm B}(n+m,p)$.

In the above, we used the following:

Lemma

For any positive integers $n$, $m$, and $k\le n+m$: $$ \sum_{i=0}^{k} {n\choose i}{m\choose k-i} = {n+m\choose k}. $$

Proof: Apply the Binomial Theorem to the equality
$$ (1+x)^n(1+x)^m=(1+x)^{n+m} $$ to obtain $$\tag{1} \sum_{i=0}^n{n\choose i}x^{n-i}\cdot\sum_{j=0}^m{m\choose j}x^{m-j}=\sum_{k=0}^{n+m}{n+m\choose k}x^{n+m-k}. $$ But $$ \eqalign{ \sum_{i=0}^n{n\choose i}x^{n-i}\cdot\sum_{j=0}^m{m\choose j}x^{m-j} &=\sum_{i=0}^n{n\choose i}\cdot\Bigl[\sum_{j=0}^m{m\choose j}x^{m-j}\bigr]x^{n-i}\cr &=\sum_{i=0}^n\Bigl[\sum_{j=0}^m{n\choose i}{m\choose j}x^{n+m-(i+j)}\Bigr].\cr } $$ Now, terms of the form $x^{n+m-k}$ on the right hand side of the above equality are obtained only when $0\le i\le k$ and $j=k-i$. Thus, the $x^{n+m-k}$-th term of the left hand side of equation $(1)$ is: $$ \sum_{i=0}^k{n\choose i}{m\choose k-i}x^{m+n-k}. $$ Since the $x^{n+m-k}$-th term of the right hand side of equation $(1)$ is $$ {n+m\choose k}x^{n+m-k}, $$ we have $$ \sum_{i=0}^k{n\choose i}{m\choose k-i}={n+m\choose k}, $$ as desired.


Convolution Theorem:

The probability mass function of the sum of two independent discrete variables is the convolution of their probability mass functions:

Let $X_1$ and $X_2$ be independent, discrete random variables that take integer values with respective probability mass functions $p_{X_1}$ and $p_{X_2}$. Let $Y=X_1+X_2$. Then for each admissable $k$: $$ p_Y(k)=\sum_{i\le\, k}p_{X_1}(i)p_{X_2}(k-i). $$

The sum appearing on the right hand side of the above equality is called the convolution of $p_{X_1}$ and $p_{X_2}$.

Proof: Exercise.

share|improve this answer

The binomially distributed random variable $X$ records the number of successes if we repeat an experiment independently $m$ times, with probability of success each time equal to $p$. The random variable $Y$ records the the number of successes in $n$ independent trials, and we are told that $X$ and $Y$ are independent.

Define Bernoulli random variables $W_1, W_2, \dots, W_m, W_{m+1}, W_{m+2}, \dots, W_{m+n}$ as follows. Perform an experiment independently $m+n$ times, where the probability of success each time is $p$. Let $$W=\sum_{i=1}^{m+n} W_i.$$ Then $W$ has binomial distribution with parameters $m+n$, $p$. Note that $S=\sum_{i=1}^m W_i$ has binomial distribution with parameters $m$, $p$, and that $T=\sum_{i=m+1}^{m+n} W_i$ has binomial distribution with parameters $n$, $p$. So $S$ has the same distribution as $X$, and $T$ has the same distribution as $Y$.

Note also that $S$ and $T$ are independent. Since the distribution of $X+Y$ is completely determined by the distributions of $X$ and $Y$, we conclude that $X+Y$ has the same distribution as $S+T$. But $S+T=W$, so $X+Y$ is binomially distributed with parameters $m+n$, $p$.

Remark: Informally, $X+Y$ records the total number of successes in $m+n$ independent trials, where the probability of success on any trial is $p$. So it is "obvious" that $X+Y$ has binomial distribution, and there is nothing much to the argument above. However, showing that if $X$ and $Y$ are independent, then the Bernoulli components of $X$ and $Y$ are independent looks as if it may require some work. That was the reason for the workaround that used the fact that the distribution of $X+Y$ is completely determined by the individual distributions.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.